Regional Notary Supervisory Council in Handling Violations of the Notary Code of Ethics Related to Non-Compliance with the Reading of Deeds Before the Presentative and Witnesses - Diana Putri Sovia; Dita Perwitasari (Universitas Negeri Surabaya, 2026)
This research examines the function of the Regional Supervisory Council (MPD) according to the Law on the Position of Notaries (UUJN) in dealing with violations of electronic codes, especially violations of the obligation to read deeds in the presence of an audience and at least two witnesses. Using a juridical-normative approach, the study deepens the UUJN text, electronic code, and derivative regulations. MPD acts as a recipient of initial complaints from the public, carrying out initial examinations objectively and transparently. Even though it does not impose direct sanctions, the MPD produces recommendations to the Regional Supervisory Council (MPW) and the Center so that sanctions can be implemented according to determines. UUJN requires the notary to read the deed in the presence of at least two witnesses unless the person has read it himself and stated it officially. This violation causes the deed to lose its authentic status and is only valuable as a private deed. The MPW can give verbal or written warnings, while the Central Supervisory Council (MPP) or the Ministry of Law and Human Rights has the authority to impose sanctions of temporary suspension or civil service, depending on the seriousness of the violation. The results of the research show that this multi-level supervision system creates effectiveness and danger in maintaining the professional integrity of notaries. However, its effectiveness is still limited by low public awareness of notary procedures and lack of participation in the complaints process. Therefore, recommendations are directed at: (1) strengthening MPD institutional capacity; (2) increasing socialization of UUJN and electronic codes to the community; and (3) increasing the capabilities of MPD members in supervision and development. This step is expected to increase notaries' compliance with their deed reading obligations and strengthen public trust in the notarial profession.